ANDROGINIA COMO IDENTIDADE CONTEMPORÂNEA: A CONSTRUÇÃO DO ETHOS EM REVISTAS NACIONAIS São Bernardo - PISA, LÍCIA FREZZA (2017)
It's notorious how the subject of identity acquired importance lately and how gender diversity, strongly influenced by feminism, develop as new forms of identification emerge. Closed identities gives way to plural identities, such as androgyny, and it becomes necessary to understand how the media builds the image of that identity. Therefore, this work seeks to understand the construction of the androgynous identity using the magazine media. By means of the French Discourse Analysis, we studied the construction of the ethos starting from the constituting elements of the androgynous identity representation and analyzed whether there is an androgyny pattern that is endorsed or deconstructed by the media, as well as if there were differences in the construction of the ethos in different types of magazines or if they remained the same. The corpus has 80 articles, comprising twenty-one different magazines in nine categories, during the period from 1993 to 2015. As a hypothesis, we consider that the discursive universe legitimating the construction of the image of the androgyne is the fashion one and, if proven, it will be necessary to observe if this representation is marked by the cultural discourse of questioning the gender and commercial, which propose new forms of consumption. We conclude that the androgyne is legitimized by the fashion discursive universe, in which there are both a political appeal for gender questioning, as a commercial contribution, introducing a form of identity through the consumption of certain products/signs. The androgyne was analyzed by means of the ethos and we found that such identity reflects the bold, the libertarian and the revolutionary as symbolic values.